Carbon fiber reinforced silicon carbide brake disc and preparation method thereof

By using carbon fiber gingham cloth stacking and adjusting the silicon carbide content, the problem of insufficient strength and wear resistance of existing brake disc materials is solved, and the preparation of high-performance carbon ceramic brake discs is realized, which improves the overall strength and friction coefficient of the material.

CN119778399AActive Publication Date: 2025-04-08深圳市佰斯倍新材料科技有限公司

Patent Information

Application Number
CN202411721791.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-04-08
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The existing brake discs have limitations in fiber content and mesh density, resulting in limited material strength improvement. The carbon ceramic brake disc components prepared by traditional processes are basically the same in the thickness direction, which is not conducive to the material performance requirements of high wear resistance on the surface and high strength of the substrate.

Method used

The carbon fiber gingham cloth is used for stacking hot pressing to reduce the needle puncture process. By adjusting the silicon carbide content in different areas, a combined structure of the long fiber area and the short fiber area is designed to improve the overall strength and friction coefficient of the brake disc.

Benefits of technology

The high performance improvement of the brake disc is achieved, ensuring the strength of the material at the connection and surface wear resistance, while simplifying the preparation process and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119778399A_ABST
    Figure CN119778399A_ABST
Patent Text Reader

Abstract

The invention provides a carbon fiber reinforced silicon carbide brake disc. The carbon fiber reinforced silicon carbide brake disc comprises a long fiber area I, a long fiber area II, a short fiber area III, a long fiber area IV and a long fiber area V. The long fiber area II and the long fiber area IV are the same in component, and the long fiber area I and the long fiber area V are the same in component. Each of the long fiber region I and the long fiber region V comprises one long fiber layer, two long fiber layers,..., Nm long fiber layers, and from the first long fiber layer on the surface to the Nn long fiber layers, the silicon carbide content VSiCn in the Nn long fiber layers is reduced by 1lt along with the increase of the number of layers; n < nlt >; nm. Each long fiber layer in the long fiber area extends from the surface of the brake disc to the inside, the content of silicon carbide in the long fiber layer is gradually reduced, it is guaranteed that the content of silicon carbide in the surface long fiber layer is high, and the brake disc has a good friction coefficient; and the phenomenon that a large amount of residual thermal stress occurs due to different sharp changes of the silicon carbide content of the multi-layer material can be avoided, and the material strength is effectively guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of brake disc manufacturing, and in particular to a carbon fiber reinforced silicon carbide brake disc and a preparation method thereof. Background Art

[0002] The brake disc is an important component installed on vehicles such as cars and motorcycles, used to brake the vehicle. It is usually located between the wheels and works with the brake caliper, brake pads, etc. in the brake system. The brake disc mainly plays the role of deceleration or emergency stop during the operation of the car. It is related to human life safety in emergencies, so it is particularly important. Brake discs are divided into two common types: metal brake discs and carbon ceramic brake discs. Metal brake discs are usually made of cast iron, steel or aluminum alloy, and have durability and high braking performance. Carbon ceramic brake discs are made of carbon fiber and ceramic materials, and have the characteristics of lighter weight, higher braking performance and wear resistance, and are suitable for high-performance vehicles. At present, brake discs are generally prepared by unidirectional cloth and mesh lamination needle punching to prepare the base layer. The carbon fiber content in the blank prepared by lamination needle punching is low, often only 30-35vol%, and the density of the mesh is low, which limits the total carbon fiber content, and the low fiber content limits the further improvement of the material strength. And the needle punching process is accompanied by the destruction of the fiber, which has a great influence on the strength of the fiber composite material. In addition, the components of carbon ceramic brake discs prepared by traditional processes are basically the same in the thickness direction, which is not conducive to the material performance requirements of high wear resistance on the surface and high strength of the matrix. In this regard, a friction layer will be added outside the matrix layer to improve the wear resistance of the brake disc. To prepare the friction layer separately, the sample needs to undergo the vapor deposition process CVI before preparing the friction layer, and then carbonize to remove organic matter in the friction layer blank, and finally perform siliconization. The preparation process is cumbersome and costly.

[0003] In this regard, a carbon fiber reinforced silicon carbide brake disc is proposed. Carbon fiber lattice cloth is used for lamination and hot pressing to reduce the needling process. By adjusting the silicon carbide content in different areas of the brake disc, the brake disc has a good friction coefficient while ensuring the overall strength of the brake disc. Summary of the invention

[0004] The present invention aims to provide a high-performance carbon-ceramic brake disc, which can improve the material strength of the brake disc joint and prevent cracking by setting different carbon fiber contents and fiber orientations in different areas.

[0005] To achieve this purpose, the present invention provides a carbon fiber reinforced silicon carbide brake disc. The carbon fiber reinforced silicon carbide brake disc includes a long fiber zone I, a long fiber zone II, a short fiber zone III, a long fiber zone IV, and a long fiber zone V. It is characterized in that the long fiber zone II and the long fiber zone IV are respectively arranged on both sides of the short fiber zone III and are symmetric about the central axis in the height direction of the short fiber zone III. The long fiber zone I is arranged on the side of the long fiber zone II away from the short fiber zone III, and the long fiber zone V is arranged on the side of the long fiber zone IV away from the short fiber zone III. The long fiber zone I and the long fiber zone V are symmetric about the central axis in the height direction of the short fiber zone III. The components of the long fiber zone II and the long fiber zone IV are the same, and the components of the long fiber zone I and the long fiber zone V are the same. Both the long fiber zone I and the long fiber zone V include 1 layer of long fiber layer, 2 layers of long fiber layer... Nm layers of long fiber layer. The 1 layer of long fiber layer is away from the short fiber zone III and the silicon carbide content in the 1 layer of long fiber layer is V SiCf , the Nm layer of long fiber layer is close to the short fiber zone III and the silicon carbide content in the Nm layer of long fiber layer is V SiCb , starting from the 1 layer of long fiber layer on the surface to the Nn layer of long fiber layer, the silicon carbide content V in the Nn layer of long fiber layer SiCn decreases with the increase of the number of layers. 1 < Nn < Nm, and its content satisfies the following formula:

[0006]

[0007] where V SiCf is 40 - 70%, V SiCb is 30 - 50%, Nm is any natural number from 4 to 13, and k is an engineering coefficient with a value range of 0.8 - 1.2.

[0008] Preferably, both the long fiber zone II and the long fiber zone IV include M layers of long fiber layer, where M is a natural number greater than 1. The components of each layer of long fiber layer are the same. Each layer of long fiber layer contains 40 - 65% carbon, 30 - 50 vol% silicon carbide, and 3 - 13 vol% silicon.

[0009] Preferably, the short fiber zone III is a short fiber layer. The carbon content of the short fiber layer is 35 - 60%, the silicon carbide content is 35 - 55 vol%, and the silicon content is 3 - 13 vol%.

[0010] Preferably, the difference between the silicon carbide content in the short fiber zone III and the silicon carbide content in the long fiber zone II and the long fiber zone IV is less than 6%.

[0011] Preferably, the thickness of the long fiber zone I and the long fiber zone V is 0.8 - 3 mm, and the thickness of the long fiber zone II and the long fiber zone IV is 2 - 20 mm. The thickness of the short fiber region is mainly determined by the overall thickness of the brake disc and is generally 6 - 30 mm.

[0012] The present invention also provides a method for preparing a carbon fiber reinforced silicon carbide brake disc, which is used to prepare the above carbon fiber reinforced silicon carbide brake disc. The preparation method is as follows:

[0013] S1: preparing a coating slurry, wherein the coating slurry comprises a phenolic resin solution with a concentration of 50%, silicon carbide powder and a pore-forming agent, wherein the coating slurry comprises 50-95 vol% of the phenolic resin solution, 0-30 vol% of the silicon carbide powder, and the remainder is the pore-forming agent;

[0014] S2: applying the coating slurry onto a plurality of carbon fiber woven fabrics to obtain a fiber cloth for a long fiber region I and a fiber cloth for a long fiber region V, wherein the silicon carbide powder and the pore-forming agent in the coating slurry for each carbon fiber woven fabric decrease in proportion, and the phenolic resin solution increases in proportion;

[0015] S3: stacking the fiber cloth for the long fiber zone I and the fiber cloth for the long fiber zone V in the order of decreasing pore-forming agent content in the coating slurry to obtain a long fiber zone I laminated block and a long fiber zone V laminated block respectively;

[0016] S4: drying the long fiber region I laminated block and the long fiber region V laminated block until they no longer lose weight, the drying temperature is 60-70° C., and the volume proportion of the carbon fibers after drying is 30-55% of the total volume;

[0017] S5: applying the coating slurry with the least pore-forming agent content in S2 on the carbon fiber lattice cloth to obtain a plurality of fiber cloths for long fiber zone II and fiber cloths for long fiber zone IV, and stacking the fiber cloths for long fiber zone II and fiber cloths for long fiber zone IV respectively to obtain long fiber zone II laminated blocks and long fiber zone IV laminated blocks;

[0018] S6: drying the long fiber zone II laminated block and the long fiber zone IV laminated block until there is no more weight loss, the drying temperature is 60-70° C., and the volume proportion of the carbon fibers after drying is 30-55% of the total volume;

[0019] S7: Coating the carbon fiber long fiber bundle with a 50% concentration of phenolic solution, and after drying, cutting it into short fiber bundles with a uniform length of 10-30 mm; the drying temperature is 60-70° C.;

[0020] S8: placing the long fiber area I laminated block-long fiber area II laminated block-short fiber bundle-long fiber area IV laminated block-long fiber area V laminated block into a mold in the order of, wherein the long fiber area I laminated block is placed with the long fiber layer with the least pore-forming agent content facing downward, and the long fiber area V laminated block is placed with the long fiber layer with the least pore-forming agent content facing upward; then pressing and curing to obtain a green body;

[0021] S9: carbonizing the green body to obtain a carbonized green body, wherein the carbonization temperature is 900° C. and the holding time is 4-8 hours;

[0022] S10: placing the carbide blank into a boron nitride crucible, into which pure silicon powder of 1.1 times the mass of the blank is pre-placed, and then placing the boron nitride crucible containing the carbide blank into a high-temperature vacuum furnace for siliconizing treatment to obtain a silicided blank, wherein the siliconizing temperature is 1600-1700° C., the holding time is 2-4 hours, and the furnace pressure is less than 1000 Pa;

[0023] S11: performing surface grinding and outer contour dimension processing on the siliconized blank to obtain the carbon fiber reinforced silicon carbide brake disc.

[0024] The purpose of adding pore-forming agent to the coating slurry is to increase the permeability during siliconization. If there are only phenolic acid and silicon carbide, there may be blocked pores and liquid silicon cannot penetrate completely. Therefore, some pore-forming agent will be added according to the penetration situation. In addition, the content ratio of silicon carbide and silicon after siliconization can also be adjusted by pore-forming agent. If there are only silicon carbide and phenolic acid, the ratio of silicon carbide to silicon after siliconization is fixed. The more pore-forming agent is used, the more silicon will remain after siliconization.

[0025] Preferably, the k value of the carbon fiber woven fabric is 3-12k.

[0026] Preferably, the pore-forming agent is PMMA plastic particles.

[0027] Preferably, the volume content of the short fiber bundles after drying in S7 is 25-50%.

[0028] Preferably, the pressing conditions in S8 are: pressure of 2-20 MPa, temperature of 150° C., and time of 2-3 h.

[0029] Beneficial effects: The carbon fiber reinforced silicon carbide brake disc provided by the present invention replaces the commonly used carbon fiber unidirectional cloth and mesh tire lamination needle-punching method by adopting the lattice cloth lamination method. Since the lattice cloth lamination does not have a needle-punching process, the strength of the long fiber layer can be effectively improved. The core adopts short fibers as the matrix, and the short fibers and long fibers are combined. The outer layer is in direct contact with the brake pad, and the force is more complicated, and the mechanical properties of the material on the surface of the brake disc are required to be high; and the thermal conductivity of the long fiber is higher than that of the short fiber, which is conducive to the heat dissipation of the brake disc surface and avoids the temperature from rising sharply on the disc surface. And each layer of long fiber layer in the long fiber area gradually decreases in the direction of extending from the surface of the brake disc to the inside, ensuring that the silicon carbide content in the surface long fiber layer is high, so that the brake disc has a good friction coefficient, and the silicon carbide content gradually decreases with the increase in the number of layers, avoiding the phenomenon that a large amount of residual thermal stress appears due to the sharp change of silicon carbide content in multi-layer materials, and effectively ensuring the strength of the material. According to the wear resistance requirements of the long fiber area I and the long fiber area V and the connection strength requirements of the brake disc, the present invention proposes a calculation formula for the silicon carbide content of each long fiber layer in the long fiber area I and the long fiber area V as the number of layers changes, and the slurry ratio is designed according to the actual brake disc requirements during the auxiliary preparation process. In addition, the present invention also proposes a method for preparing a carbon fiber reinforced silicon carbide brake disc, which has a simple preparation process, uses carbon fiber lattice cloth to apply slurry in different ratios, thereby realizing a gradual change of the silicon carbide content of the brake disc from the outside to the inside, and the operation method is simple and easy to produce. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a schematic diagram of the structure of the carbon fiber reinforced silicon carbide brake disc of the present invention.

[0031] In the figure: 1-long fiber zone I, 2-long fiber zone II, 3-short fiber zone III, 4-long fiber zone IV, 5-long fiber zone V. DETAILED DESCRIPTION

[0032] The embodiments described below are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] refer to Figure 1, the present invention provides a carbon fiber reinforced silicon carbide brake disc, the carbon fiber reinforced silicon carbide brake disc includes a long fiber region I1, a long fiber region II2, a short fiber region III3, a long fiber region IV4 and a long fiber region V5, characterized in that the long fiber region II2 and the long fiber region IV4 are respectively arranged on both sides of the short fiber region III3 and are symmetric about the central axis in the height direction of the short fiber region III3, the long fiber region I1 is arranged on the side of the long fiber region II2 away from the short fiber region III3, the long fiber region V5 is arranged on the side of the long fiber region IV4 away from the short fiber region III3, and the long fiber region I1 and the long fiber region V5 are symmetric about the central axis in the height direction of the short fiber region III3; the components of the long fiber region II2 and the long fiber region IV4 are the same, and the components of the long fiber region I1 and the long fiber region V5 are the same; both the long fiber region I and the long fiber region V include 1 layer of long fiber layer, 2 layers of long fiber layer... Nm layers of long fiber layer, 1 layer of long fiber layer is far from the short fiber region III and the silicon carbide content in 1 layer of long fiber layer is V SiCf , Nm layers of long fiber layer are close to the short fiber region III and the silicon carbide content in Nm layers of long fiber layer is V SiCb , from the surface 1 layer of long fiber layer to Nn layers of long fiber layer, the silicon carbide content V in Nn layers of long fiber layer SiCn decreases with the increase of the number of layers, 1 < Nn < Nm, and its content satisfies the following formula:

[0034]

[0035] where V SiCf is 40 - 70%, V SiCb is 30 - 50%, Nm is any natural number from 4 to 13, and k is an engineering coefficient, and its value range is 0.8 - 1.2.

[0036] Both the long fiber region II and the long fiber region IV include M layers of long fiber layer, M is a natural number greater than 1, the components of each layer of long fiber layer are the same, and each layer of long fiber layer contains 40 - 65% carbon, 30 - 50 vol% silicon carbide and 3 - 13 vol% silicon.

[0037] The short fiber region III is a short fiber layer, the carbon content of the short fiber layer is 35 - 60%, the silicon carbide content is 35 - 55 vol%, and the silicon content is 3 - 13 vol%.

[0038] The difference between the silicon carbide content in the short fiber region III and the silicon carbide content in the long fiber region II and the long fiber region IV is less than 6%.

[0039] The thickness of the long fiber region I and the long fiber region V is 0.8 - 3 mm, and the thickness of the long fiber region II and the long fiber region IV is 2 - 20 mm.

[0040] Example 1

[0041] This embodiment provides a carbon fiber reinforced silicon carbide brake disc, and the preparation steps are as follows:

[0042] S1: preparing a coating slurry, the coating slurry comprising a phenolic resin solution with a concentration of 50%, silicon carbide powder and a pore-forming agent, the coating slurry comprising 8 layers of coating slurry, the first layer of coating slurry containing 58% phenolic resin solution (50% concentration), 24% silicon carbide powder and 18% pore-forming agent; the second layer of coating slurry containing 2% less silicon carbide powder than the first layer of coating slurry, 2% less pore-forming agent than the first layer of coating slurry, and 4% more phenolic resin solution than the first layer of coating slurry; the third layer of coating slurry containing 2% less silicon carbide powder than the second layer of coating slurry, 2% less pore-forming agent than the second layer of coating slurry, and 4% more phenolic resin solution than the second layer of coating slurry; and so on, each layer of coating slurry changes according to this ratio until the eighth layer of coating slurry;

[0043] S2: The coating slurry is respectively applied to 8 sheets of carbon fiber woven fabrics with a single bundle k value of 12k to obtain a fiber cloth for long fiber area I, and the operation is repeated to obtain a fiber cloth for long fiber area V. The silicon carbide powder and the pore-forming agent in the coating slurry for each carbon fiber woven fabric decrease in proportion, and the phenolic resin solution increases in proportion;

[0044] S3: After coating, the fiber cloth for the long fiber area I and the fiber cloth for the long fiber area V are stacked in the order of decreasing pore-forming agent content in the coating slurry to obtain a long fiber area I stacked block and a long fiber area V stacked block respectively;

[0045] S4: drying the long fiber region I laminated block and the long fiber region V laminated block until they no longer lose weight, the drying temperature is 65° C., and the volume proportion of the carbon fibers after drying is 35% of the total volume;

[0046] S5: applying the eighth layer of the slurry (i.e., the slurry with the least pore-forming agent content) on a single bundle of carbon fiber woven fabric with a k value of 12k to obtain a plurality of fiber cloths for long fiber zone II and fiber cloths for long fiber zone IV, and stacking the fiber cloths for long fiber zone II and fiber cloths for long fiber zone IV in 13 layers respectively to obtain a long fiber zone II laminated block and a long fiber zone IV laminated block;

[0047] S6: drying the long fiber zone II laminated block and the long fiber zone IV laminated block until there is no more weight loss, the drying temperature is 60° C., and the volume proportion of the carbon fibers after drying is 35% of the total volume;

[0048] S7: Coating a 50% phenolic solution on a carbon fiber long fiber bundle, and after drying, cutting it into short fiber bundles with a uniform length of 15 mm; the drying temperature is 60° C., and the volume of the carbon fiber after drying accounts for 30% of the total volume;

[0049] S8: placing the long fiber zone I laminated block-long fiber zone II laminated block-short fiber bundle-long fiber zone IV laminated block-long fiber zone V laminated block into the mold in the order of 10 mm in thickness of the short fiber bundle after pressing, wherein the long fiber zone I laminated block is placed with the long fiber layer with the least pore-forming agent content facing downward, and the long fiber zone V laminated block is placed with the long fiber layer with the least pore-forming agent content facing upward; then pressing and curing are performed to obtain a green body at a pressure of 6 MPa, a temperature of 150°C, and a time of 3 h;

[0050] S9: carbonizing the green body to obtain a carbonized green body, wherein the carbonization temperature is 900° C. and the holding time is 5 hours;

[0051] S10: placing the carbide blank into a boron nitride crucible, into which pure silicon powder of 1.1 times the mass of the blank is pre-placed, and then placing the boron nitride crucible containing the carbide blank into a high-temperature vacuum furnace for siliconizing treatment to obtain a silicided blank, wherein the siliconizing temperature is 1700° C., the holding time is 4 hours, and the furnace pressure is less than 1000 Pa;

[0052] S11: performing surface grinding and outer contour dimension processing on the siliconized blank to obtain the carbon fiber reinforced silicon carbide brake disc.

[0053] Example 2

[0054] This embodiment provides a carbon fiber reinforced silicon carbide brake disc, and the preparation steps are as follows:

[0055] S1: preparing a coating slurry, the coating slurry comprising a phenolic resin solution with a concentration of 50%, silicon carbide powder and a pore-forming agent, the coating slurry comprising 8 layers of coating slurry, the first layer of coating slurry having a phenolic resin solution (50% concentration) content of 56%, a silicon carbide powder content of 22%, and a pore-forming agent content of 22%; the second layer of coating slurry having a silicon carbide powder content of 2% less than that of the first layer of coating slurry, a pore-forming agent content of 2% less than that of the first layer of coating slurry, and a phenolic resin solution content of 4% more than that of the first layer of coating slurry; the third layer of coating slurry having a silicon carbide powder content of 2% less than that of the second layer of coating slurry, a pore-forming agent content of 2% less than that of the second layer of coating slurry, and a phenolic resin solution content of 4% more than that of the second layer of coating slurry; and so on, each layer of coating slurry changes according to this ratio until the eighth layer of coating slurry;

[0056] S2: Apply the coating slurry to 8 sheets of carbon fiber woven fabrics with a single bundle k value of 12k to obtain a fiber cloth for long fiber area I, and repeat the operation to obtain a fiber cloth for long fiber area V. The silicon carbide powder and the pore-forming agent in the coating slurry for each carbon fiber woven fabric decrease in proportion, and the phenolic resin solution increases in proportion;

[0057] S3: after coating, the fiber cloths of the long fiber area I are stacked in the order of decreasing pore-forming agent content in the coating slurry to obtain a long fiber area I laminated block, and the fiber cloths of the long fiber area V after coating are stacked in the order of decreasing pore-forming agent content in the coating slurry to obtain a long fiber area V laminated block;

[0058] S4: drying the long fiber region I laminated block and the long fiber region V laminated block until they no longer lose weight, the drying temperature is 65° C., and the volume proportion of the carbon fibers after drying is 35% of the total volume;

[0059] S5: applying the eighth layer of the slurry on a single bundle of carbon fiber woven fabric with a k value of 12k to obtain a plurality of fiber cloths for long fiber zone II and fiber cloths for long fiber zone IV, and stacking the fiber cloths for long fiber zone II and fiber cloths for long fiber zone IV in 13 layers respectively to obtain a long fiber zone II laminated block and a long fiber zone IV laminated block;

[0060] S6: drying the long fiber zone II laminated block and the long fiber zone IV laminated block until there is no more weight loss, the drying temperature is 60° C., and the volume proportion of the carbon fibers after drying is 35% of the total volume;

[0061] S7: Coating a 50% phenolic solution on a carbon fiber long fiber bundle, and after drying, cutting it into short fiber bundles with a uniform length of 15 mm; the drying temperature is 60° C., and the volume of the carbon fiber after drying accounts for 30% of the total volume;

[0062] S8: placing the long fiber zone I laminated block-long fiber zone II laminated block-short fiber bundle-long fiber zone IV laminated block-long fiber zone V laminated block into the mold in the order of 10 mm in thickness of the short fiber bundle after pressing, wherein the long fiber zone I laminated block is placed with the long fiber layer with the least pore-forming agent content facing downward, and the long fiber zone V laminated block is placed with the long fiber layer with the least pore-forming agent content facing upward; then pressing and curing are performed to obtain a green body at a pressure of 6 MPa, a temperature of 150°C, and a time of 3 h;

[0063] S9: carbonizing the green body to obtain a carbonized green body, wherein the carbonization temperature is 900° C. and the holding time is 5 hours;

[0064] S10: placing the carbide blank into a boron nitride crucible, into which pure silicon powder of 1.1 times the mass of the blank is pre-placed, and then placing the boron nitride crucible containing the carbide blank into a high-temperature vacuum furnace for siliconizing treatment to obtain a silicided blank, wherein the siliconizing temperature is 1600° C., the holding time is 4 hours, and the furnace pressure is less than 1000 Pa;

[0065] S11: performing surface grinding and outer contour dimension processing on the siliconized blank to obtain the carbon fiber reinforced silicon carbide brake disc.

[0066] Example 3

[0067] This embodiment provides a carbon fiber reinforced silicon carbide brake disc, and the preparation steps are as follows:

[0068] S1: preparing a coating slurry, the coating slurry comprising a phenolic resin solution with a concentration of 50%, silicon carbide powder and a pore-forming agent, the coating slurry comprising 8 layers of coating slurry, the first layer of coating slurry containing 58% phenolic resin solution (50% concentration), 24% silicon carbide powder and 18% pore-forming agent; the second layer of coating slurry containing 2% less silicon carbide powder than the first layer of coating slurry, 2% less pore-forming agent than the first layer of coating slurry, and 4% more phenolic resin solution than the first layer of coating slurry; the third layer of coating slurry containing 2% less silicon carbide powder than the second layer of coating slurry, 2% less pore-forming agent than the second layer of coating slurry, and 4% more phenolic resin solution than the second layer of coating slurry; and so on, each layer of coating slurry changes according to this ratio until the eighth layer of coating slurry;

[0069] S2: Apply the coating slurry to 8 sheets of carbon fiber woven fabrics with a single bundle k value of 12k to obtain a fiber cloth for long fiber area I, and repeat the operation to obtain a fiber cloth for long fiber area V. The silicon carbide powder and the pore-forming agent in the coating slurry for each carbon fiber woven fabric decrease in proportion, and the phenolic resin solution increases in proportion;

[0070] S3: after coating, the fiber cloths of the long fiber area I are stacked in the order of decreasing pore-forming agent content in the coating slurry to obtain a long fiber area I laminated block, and the fiber cloths of the long fiber area V after coating are stacked in the order of decreasing pore-forming agent content in the coating slurry to obtain a long fiber area V laminated block;

[0071] S4: drying the long fiber region I laminated block and the long fiber region V laminated block until they no longer lose weight, the drying temperature is 65° C., and the volume proportion of the carbon fibers after drying is 35% of the total volume;

[0072] S5: applying the eighth layer of the slurry on a single bundle of carbon fiber woven fabric with a k value of 12k to obtain a plurality of fiber cloths for long fiber zone II and fiber cloths for long fiber zone IV, and stacking the fiber cloths for long fiber zone II and fiber cloths for long fiber zone IV in 13 layers respectively to obtain a long fiber zone II laminated block and a long fiber zone IV laminated block;

[0073] S6: drying the long fiber zone II laminated block and the long fiber zone IV laminated block until there is no more weight loss, the drying temperature is 60° C., and the volume proportion of the carbon fibers after drying is 35% of the total volume;

[0074] S7: Coating a 50% phenolic solution on a carbon fiber long fiber bundle, and after drying, cutting it into short fiber bundles with a uniform length of 15 mm; the drying temperature is 60° C., and the volume proportion of the carbon fiber after drying is 35% of the total volume;

[0075] S8: placing the long fiber zone I laminated block-long fiber zone II laminated block-short fiber bundle-long fiber zone IV laminated block-long fiber zone V laminated block into the mold in the order of 10 mm in thickness of the short fiber bundle after pressing, wherein the long fiber zone I laminated block is placed with the long fiber layer with the least pore-forming agent content facing downward, and the long fiber zone V laminated block is placed with the long fiber layer with the least pore-forming agent content facing upward; then pressing and curing are performed to obtain a green body at a pressure of 6 MPa, a temperature of 150°C, and a time of 3 h;

[0076] S9: carbonizing the green body to obtain a carbonized green body, wherein the carbonization temperature is 900° C. and the holding time is 5 hours;

[0077] S10: placing the carbide blank into a boron nitride crucible, into which pure silicon powder of 1.1 times the mass of the blank is pre-placed, and then placing the boron nitride crucible containing the carbide blank into a high-temperature vacuum furnace for siliconizing treatment to obtain a silicided blank, wherein the siliconizing temperature is 1700° C., the holding time is 4 hours, and the furnace pressure is less than 1000 Pa;

[0078] S11: grinding the surface of the siliconized blank and processing the outer contour dimensions to obtain the carbon fiber reinforced silicon carbide brake disc.

[0079] Comparative Example 1

[0080] This comparative example provides a carbon fiber reinforced silicon carbide brake disc, and the preparation steps are as follows:

[0081] S1: preparing a coating slurry, wherein the coating slurry comprises a phenolic resin solution with a concentration of 50%, silicon carbide powder and a pore-forming agent, wherein the content of the phenolic resin solution (50% concentration) in the coating slurry is 58%, the content of the silicon carbide powder is 24%, and the content of the pore-forming agent is 18%;

[0082] S2: applying the coating slurry onto 8 sheets of carbon fiber woven fabrics with a single bundle k value of 12k to obtain a fiber cloth for a long fiber region I and a fiber cloth for a long fiber region V;

[0083] S3: after painting, the long fiber area I is stacked with fiber cloth in sequence to obtain a long fiber area I laminated block, and the painted long fiber area V is stacked with fiber cloth in sequence to obtain a long fiber area V laminated block;

[0084] S4: drying the long fiber region I laminated block and the long fiber region V laminated block until there is no more weight loss, the drying temperature is 60° C., and the volume proportion of the carbon fibers after drying is 35% of the total volume;

[0085] S5: applying the slurry on a single bundle of carbon fiber woven fabric with a k value of 12k to obtain a plurality of fiber cloths for long fiber zone II and fiber cloths for long fiber zone IV, and stacking the fiber cloths for long fiber zone II and fiber cloths for long fiber zone IV for 13 layers respectively to obtain a long fiber zone II laminated block and a long fiber zone IV laminated block;

[0086] S6: drying the long fiber zone II laminated block and the long fiber zone IV laminated block until there is no more weight loss, the drying temperature is 60° C., and the volume proportion of the carbon fibers after drying is 35% of the total volume;

[0087] S7: Coating a 50% phenolic solution on a carbon fiber long fiber bundle, and after drying, cutting it into short fiber bundles with a uniform length of 15 mm; the drying temperature is 60° C., and the volume of the carbon fiber after drying accounts for 30% of the total volume;

[0088] S8: placing the long fiber area I laminated block-long fiber area II laminated block-short fiber bundle-long fiber area IV laminated block-long fiber area V laminated block into the mold in the order; then pressing and curing to obtain a green body, the pressure is 6MPa, the temperature is 150℃, the time is 3h, and the thickness of the short fiber bundle after pressing is 10mm;

[0089] S9: carbonizing the green body to obtain a carbonized green body, wherein the carbonization temperature is 900° C. and the holding time is 5 hours;

[0090] S10: placing the carbide blank into a boron nitride crucible, into which pure silicon powder of 1.1 times the mass of the blank is pre-placed, and then placing the boron nitride crucible containing the carbide blank into a high-temperature vacuum furnace for siliconizing treatment to obtain a silicided blank, wherein the siliconizing temperature is 1700° C., the holding time is 4 hours, and the furnace pressure is less than 1000 Pa;

[0091] S11: performing surface grinding and outer contour dimension processing on the siliconized blank to obtain the carbon fiber reinforced silicon carbide brake disc.

[0092] Comparative Example 2

[0093] This embodiment provides a carbon fiber reinforced silicon carbide brake disc, and the preparation steps are as follows:

[0094] S1: preparing a coating slurry, the coating slurry comprising a phenolic resin solution with a concentration of 50%, silicon carbide powder and a pore-forming agent, the coating slurry comprising three layers of coating slurry, the first layer of coating slurry containing 58% phenolic resin solution (50% concentration), 24% silicon carbide powder and 18% pore-forming agent; the second layer of coating slurry containing 18% silicon carbide powder, 11% pore-forming agent and 71% phenolic resin solution; the third layer of coating slurry containing 10% silicon carbide powder, 4% pore-forming agent and 86% phenolic resin solution;

[0095] S2: applying the coating slurry to three sheets of carbon fiber woven fabrics with a single bundle k value of 12k to obtain a fiber cloth for a long fiber region I and a fiber cloth for a long fiber region V;

[0096] S3: after coating, the fiber cloth for the long fiber area I and the fiber cloth for the long fiber area V are stacked in the order of decreasing pore-forming agent content in the coating slurry to obtain a long fiber area I stacked block and a long fiber area V stacked block;

[0097] S4: drying the long fiber region I laminated block and the long fiber region V laminated block until there is no more weight loss, the drying temperature is 60° C., and the volume proportion of the carbon fibers after drying is 35% of the total volume;

[0098] S5: applying the third layer of slurry on a single bundle of carbon fiber woven fabric with a k value of 12k to obtain a plurality of fiber cloths for long fiber zone II and fiber cloths for long fiber zone IV, and stacking the fiber cloths for long fiber zone II and fiber cloths for long fiber zone IV in 13 layers respectively to obtain a long fiber zone II laminated block and a long fiber zone IV laminated block;

[0099] S6: drying the long fiber zone II laminated block and the long fiber zone IV laminated block until there is no more weight loss, the drying temperature is 60° C., and the volume proportion of the carbon fibers after drying is 35% of the total volume;

[0100] S7: Coating a 50% phenolic solution on a carbon fiber long fiber bundle, and after drying, cutting it into short fiber bundles with a uniform length of 15 mm; the drying temperature is 60° C., and the volume of the carbon fiber after drying accounts for 30% of the total volume;

[0101] S8: placing the long fiber zone I laminated block-long fiber zone II laminated block-short fiber bundle-long fiber zone IV laminated block-long fiber zone V laminated block into the mold in the order of 10 mm in thickness of the short fiber bundle after pressing, wherein the long fiber zone I laminated block is placed with the long fiber layer with the least pore-forming agent content facing downward, and the long fiber zone V laminated block is placed with the long fiber layer with the least pore-forming agent content facing upward; then pressing and curing are performed to obtain a green body at a pressure of 6 MPa, a temperature of 150°C, and a time of 3 h;

[0102] S9: carbonizing the green body to obtain a carbonized green body, wherein the carbonization temperature is 900° C. and the holding time is 4 hours;

[0103] S10: placing the carbide blank into a boron nitride crucible, into which pure silicon powder of 1.1 times the mass of the blank is pre-placed, and then placing the boron nitride crucible containing the carbide blank into a high-temperature vacuum furnace for siliconizing treatment to obtain a silicided blank, wherein the siliconizing temperature is 1700° C., the holding time is 4 hours, and the furnace pressure is less than 1000 Pa;

[0104] S11: grinding the surface of the siliconized blank and processing the outer contour dimensions to obtain the carbon fiber reinforced silicon carbide brake disc.

[0105] The carbon fiber reinforced silicon carbide brake discs prepared in the above examples 1-3 and comparative examples 1-2 were tested. The test method is:

[0106] The dynamic friction coefficient and wear rate of the carbon ceramic brake disc sample were tested using the MM-1000 friction tester. The effective friction surface of the test ring has an outer diameter of D75mm / inner diameter of D55mm×10mm, and a specific pressure of 98N / cm 2 , inertia is 3kgf·cm·s 2 , linear speed is 25m / s.

[0107] Check whether there are cracks in the long fiber area: Test according to the test method specified in QC / T 316. Use 0.6g equivalent braking torque, braking times 20×10 4 times, check whether the connection hole is cracked every 50,000 times, and cycle a total of 300,000 times.

[0108] The test data is shown in Table 1.

[0109] Table 1 Test data of carbon fiber reinforced silicon carbide brake discs of Examples 1-3 and Comparative Examples 1-2 (the outer layer is the first layer, and the number of layers increases gradually from the outside to the inside)

[0110]

[0111] It can be seen from the above test data that in Example 1, there are 8 fiber layers in the long fiber zone I / V, and the silicon carbide content gradually decreases from the surface to the core, which effectively alleviates the thermal stress caused by different silicon carbide contents, and the silicon carbide content in the surface layer is high, ensuring the friction coefficient; Example 2 increases the silicon carbide content of the surface coating slurry, and the friction coefficient of the obtained product is improved; Example 3 increases the volume fraction of the short fiber after the coating slurry is dried, and the silicon carbide content in the short fiber zone is reduced, which alleviates the difference in expansion coefficient between the long fiber zone II / IV and the short fiber zone; in Comparative Example 1, the silicon carbide content in the long fiber zone I / V does not change gradually, and there is a large amount of residual stress at the interface between the long fiber zone I / V and the long fiber zone II / IV. After testing, a large number of cracks appear in the long fiber zone; in Comparative Example 2, there are only three layers in the long fiber zone I / V, and the silicon carbide content in these three layers changes sharply, which also leads to the generation of a large amount of residual thermal stress. Obvious cracks also appear in the long fiber zone during the test.

[0112] The above disclosures are only several preferred embodiments of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. Therefore, equivalent changes made according to the scope of the patent application of the present invention are still within the scope covered by the present invention.

Claims

1. A carbon fiber reinforced silicon carbide brake disc, comprising a long fiber area I, a long fiber area II, a short fiber area III, a long fiber area IV and a long fiber area V, characterized in that: The long fiber zone II and the long fiber zone IV are respectively arranged on both sides of the short fiber zone III and are symmetric about the central axis in the height direction of the short fiber zone III. The long fiber zone I is arranged on the side of the long fiber zone II away from the short fiber zone III. The long fiber zone V is arranged on the side of the long fiber zone IV away from the short fiber zone III. The long fiber zone I and the long fiber zone V are symmetric about the central axis in the height direction of the short fiber zone III. The compositions of the long fiber zone II and the long fiber zone IV are the same. The compositions of the long fiber zone I and the long fiber zone V are the same. Both the long fiber zone I and the long fiber zone V include 1 layer of long fiber layer, 2 layers of long fiber layer... Nm layers of long fiber layer. The 1 layer of long fiber layer is away from the short fiber zone III and the silicon carbide content in the 1 layer of long fiber layer is V SiCf , the Nm layer of long fiber layer is close to the short fiber zone III and the silicon carbide content in the Nm layer of long fiber layer is V SiCb , starting from the 1 layer of long fiber layer on the surface to the Nn layer of long fiber layer, the silicon carbide content V in the Nn layer of long fiber layer SiCn decreases with the increase of the number of layers, 1 < Nn < Nm, and its content satisfies the following formula: Where V SiCf 40-70%, V SiCb is 30-50%, Nm is any natural number between 4 and 13, and k is an engineering coefficient with a value range of 0.8-1.

2.

2. The carbon fiber reinforced silicon carbide brake disc according to claim 1, characterized in that: The long fiber zone II and the long fiber zone IV both include M long fiber layers, where M is a natural number greater than 1, and each long fiber layer has the same components, and each long fiber layer contains 40-65% carbon, 30-50 vol% silicon carbide and 3-13 vol% silicon.

3. The carbon fiber reinforced silicon carbide brake disc according to claim 1, characterized in that: The short fiber zone III is a short fiber layer, and the carbon content of the short fiber layer is 35-60%, the silicon carbide content is 35-55 vol%, and the silicon content is 3-13 vol%.

4. The carbon fiber reinforced silicon carbide brake disc according to claim 3, characterized in that: The difference between the silicon carbide content in the short fiber zone III and the silicon carbide content in the long fiber zone II and the long fiber zone IV is less than 6%.

5. The carbon fiber reinforced silicon carbide brake disc according to any one of claims 1 or 2, characterized in that: The thickness of the long fiber zone I and the long fiber zone V is 0.8-3 mm, and the thickness of the long fiber zone II and the long fiber zone IV is 2-20 mm.

6. A method for preparing a carbon fiber reinforced silicon carbide brake disc, used for preparing a carbon fiber reinforced silicon carbide brake disc as claimed in any one of claims 1 to 5, characterized in that: The preparation method is as follows: S1: preparing a coating slurry, wherein the coating slurry comprises a phenolic resin solution with a concentration of 50%, silicon carbide powder and a pore-forming agent, wherein the coating slurry comprises 50-95 vol% of the phenolic resin solution, 0-30 vol% of the silicon carbide powder, and the remainder is the pore-forming agent; S2: applying the coating slurry onto a plurality of carbon fiber woven fabrics to obtain a fiber cloth for a long fiber region I and a fiber cloth for a long fiber region V, wherein the silicon carbide powder and the pore-forming agent in the coating slurry for each carbon fiber woven fabric decrease in proportion, and the phenolic resin solution increases in proportion; S3: stacking the fiber cloth for the long fiber zone I and the fiber cloth for the long fiber zone V in the order of decreasing pore-forming agent content in the coating slurry to obtain a long fiber zone I laminated block and a long fiber zone V laminated block respectively; S4: drying the long fiber region I laminated block and the long fiber region V laminated block until they no longer lose weight, the drying temperature is 60-70° C., and the volume proportion of the carbon fibers after drying is 30-55% of the total volume; S5: applying the coating slurry with the least pore-forming agent content in S2 on the carbon fiber lattice cloth to obtain a plurality of fiber cloths for long fiber zone II and fiber cloths for long fiber zone IV, and stacking the fiber cloths for long fiber zone II and fiber cloths for long fiber zone IV respectively to obtain long fiber zone II laminated blocks and long fiber zone IV laminated blocks; S6: drying the long fiber zone II laminated block and the long fiber zone IV laminated block until there is no more weight loss, the drying temperature is 60-70° C., and the volume proportion of the carbon fibers after drying is 30-55% of the total volume; S7: Coating the carbon fiber long fiber bundle with a 50% concentration of phenolic solution, and after drying, cutting it into short fiber bundles with a uniform length of 10-30 mm; the drying temperature is 60-70° C.; S8: placing the long fiber zone I laminated block-long fiber zone II laminated block-short fiber bundle-long fiber zone IV laminated block-long fiber zone V laminated block into the mold in the order of long fiber zone I laminated block-long fiber zone II laminated block-short fiber bundle-long fiber zone IV laminated block-long fiber zone V laminated block, wherein the long fiber zone I laminated block is placed with the long fiber layer with the least pore-forming agent content facing downward, and the long fiber zone V laminated block is placed with the long fiber layer with the least pore-forming agent content facing upward; Then, pressing and solidifying are performed to obtain a green body; S9: carbonizing the green body to obtain a carbonized green body, wherein the carbonization temperature is 900° C. and the holding time is 4-8 hours; S10: placing the carbide blank into a boron nitride crucible, into which pure silicon powder of 1.1 times the mass of the blank is pre-placed, and then placing the boron nitride crucible containing the carbide blank into a high-temperature vacuum furnace for siliconizing treatment to obtain a silicided blank, wherein the siliconizing temperature is 1600-1700° C., the holding time is 2-4 hours, and the furnace pressure is less than 1000 Pa; S11: performing surface grinding and outer contour dimension processing on the siliconized blank to obtain the carbon fiber reinforced silicon carbide brake disc.

7. The method for preparing a carbon fiber reinforced silicon carbide brake disc according to claim 6, characterized in that: The k value of the carbon fiber woven fabric is 3-12k.

8. The method for preparing a carbon fiber reinforced silicon carbide brake disc according to claim 6, characterized in that: The pore-forming agent is pmma plastic particles.

9. The method for preparing a carbon fiber reinforced silicon carbide brake disc according to claim 6, characterized in that: The volume content of the short fiber bundles after drying in S7 is 25-50%.

10. The method for preparing a carbon fiber reinforced silicon carbide brake disc according to claim 6, characterized in that: The pressing conditions in S8 are: pressure of 2-20 MPa, temperature of 150°C, and time of 2-3 h.

Citation Information

Patent Citations

  • C / C-SiC composite material of sandwich structure and preparation method thereof

    CN107879758A

  • Preparation method and application of layered-structure fiber-reinforced boron carbide composite material

    CN115504800A

  • High-strength and high-toughness carbon ceramic brake disc and preparation method thereof

    CN117962432A

  • Carbon-ceramic brake disc with friction layer containing short fibers and preparation method of carbon-ceramic brake disc

    CN118622882A

  • Production method of carbon fiber-reinforced composite material and carbon fiber-reinforced composite material

    JP2014185066A

Cited By

  • Aluminum silicon carbide brake disc based on pressure infiltration process and preparation method thereof

    CN120662790A